Poetry on stage : the theatre of the Italian neo-avant-garde - Rizzo, Gianluca (Toronto Italian studies., 2020)
"Poetry on Stage focuses on exchanges between the writers of the Italian neo-avant-garde with the actors, directors, and playwrights of the Nuovo Teatro. The book sheds light on a forgotten chapter of twentieth-century Italian literature, arguing that the theatre was the ideal incubator for stylistic and linguistic experiments and a means through which authors could establish direct contact with their audience and verify the solutions they were devising to the practical and theoretical problems raised by their stances in politics and poetics. A robust textual analysis of a number of exemplary texts grounds these issues in the plays and poems produced at the time, and connects them with the experimentations subsequently carried out by some of the same artists. In-depth interviews with four of the most influential figures in the field - critic Valentina Valentini, actor and director Pippo Di Marca, author Giuliano Scabia, and the late poet Nanni Balestrini - conclude the volume, providing an invaluable first-hand testimony that brings back to life the people and controversies discussed."--